A Review on Epigenetic Effects of Environmental Factors Causing and Inhibiting Cancer - Khaledi, Fatemeh; Ghasemi, Sorayya (Current Molecular Medicine, 2022)
Epigenetic modifications refer to reversible changes in gene expression. Epigenetic changes include DNA methylation, histone modification, and non-coding RNAs that are collectively called epigenome. Various epigenetic effects account for the main impacts of environment and lifestyle on multifactorial diseases, such as cancers. The environmental impacts on cancers act as double-edged swords. While some of them are involved in cancer development, some others contribute to preventing it. In this review article, the keywords
Keywords: Epigenetic